(untitled) (Boletín Micológico, 2001)
In a farm at the province of Jujuy (Argentina), a cattle ate some mouldy bales of lucerne hay and some cows aborted immediatly after. Considering that there could be mycotoxicosis present, some samples of lucerne hay were collected and the following fungi were isolated: Myrothecium verrucaria (29,2%), Eurotium amstelodami (28,8%), Aspergillus versicolor (19,5%), Alternaria alternata (10,1%), Aspegillus ochraceus (5,28%), Penicilium aurantiogriseum (1,64%), Aspergillus flavus (0,70%), Aspergillus niger (0,47%), and others (4,33%). Ochratoxin A and aflatoxin B were detected in the fodder yet there was absence of macrocyclic trichothecenes. When the animals stopped eating the contaminated fodder, ochratoxin a was detected in the milk of one cow.